2022
DOI: 10.1051/0004-6361/202141689
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state accretion in magnetized protoplanetary disks

Abstract: Context. The transition between magnetorotational instability (MRI)-active and magnetically dead regions corresponds to a sharp change in the disk turbulence level, where pressure maxima may form, hence potentially trapping dust particles and explaining some of the observed disk substructures. Aims. We aim to provide the first building blocks toward a self-consistent approach to assess the dead zone outer edge as a viable location for dust trapping, under the framework of viscously driven accretion. Methods. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 165 publications
(223 reference statements)
2
30
0
Order By: Relevance
“…At the dead-zone outer edge, the turbulent viscosity arising from the magnetorotational instability increases from inside out. This results in a steep decrease in the gas surface density (e.g., Delage et al 2022), which can also be seen in the dust distribution (e.g., Kretke et al 2009;Ueda et al 2021c). If this is the case, a similar transition in the gas surface density, as well as the transition in the turbulence strength, should be observed.…”
Section: Surface Density Transition At 50 Aumentioning
confidence: 99%
“…At the dead-zone outer edge, the turbulent viscosity arising from the magnetorotational instability increases from inside out. This results in a steep decrease in the gas surface density (e.g., Delage et al 2022), which can also be seen in the dust distribution (e.g., Kretke et al 2009;Ueda et al 2021c). If this is the case, a similar transition in the gas surface density, as well as the transition in the turbulence strength, should be observed.…”
Section: Surface Density Transition At 50 Aumentioning
confidence: 99%
“…Furthermore, variations of the disk viscosity can also trigger spiral arms (Lyra et al 2015), but in this case numerous spiral arms would be expected, while only two are detected in current observations. However, the extension of a dead zone for a star such as LkHα 330 is expected to be around 20 au (Delage et al 2022), which is much smaller than the observed cavity. A clear way to distinguish this scenario from the planet scenario is to actually detect potential planet(s) or their circumplanetary disks inside the cavity, as in the case of PDS 70 (Keppler et al 2018;Benisty et al 2021).…”
Section: Different Radial Distribution Of the Scattered Light Millime...mentioning
confidence: 77%
“…A higher viscosity α may explain the observed accretion rate, but it is not observationally favored, as the recent study (e.g., Flaherty et al 2015) suggests that the disk viscosity may be rather low. This inconsistency is mainly due to our simplified viscous model that assumes a constant α viscosity, and more sophisticated viscous accretion (Delage et al 2022) or disk-wind accretion (Bai 2016;Suzuki et al 2016;Ida et al 2018) models are required to address this inconsistency.…”
Section: Caveatsmentioning
confidence: 99%